Classification of protective pillars toward higher safety and innovation in room-and-pillar coal mining - Prokopenko S. A. Sergey Arturovich; Sementsov V. V. Vyacheslav Vladimirovich; Dobrovolsky M. S.; Nifanov E. V. (2020, 2020)
Title screen